Encouraging Desistance from Crime - Doleac, Jennifer L. (Journal of Economic Literature, 2023)
Half of individuals released from prison in the United States will be re-incarcerated within three years, creating an incarceration cycle that is detrimental to individuals, families, and communities. There is tremendous public interest in ending this cycle, and public policies can help or hinder the reintegration of those released from jail and prison. This review summarizes the existing empirical evidence on how to intervene with existing offenders to reduce criminal behavior and improve social welfare. (JEL D91, I18, I28, I38, K42, R23)